Role of Combining Colour Doppler and Grey Scale Ultrasound in Characterizing Adnexal Masses - Gagandeep Choudhary; Avneet Boparai; Gurinder Singh; Deepak Gupta; Manjit Mohi; Sanjay Sethi (Tehran University of Medical Sciences, 2012)
Objective: To evaluate the adnexal masses with conventional gray scale and color Doppler flow imaging and to assess their diagnostic reliability to differentiate benign and malignant adnexal masses. Materials and methods: We evaluated 30 patients with adnexal mass. Morphological characterization of the mass was done using Sassone score. Color Doppler parameters noted down in each patient and Caruso vascular score was also used. The results were compared with surgical/ pathological and/or follow up scans. Results: Using sonomorphological score (Sassone) overall reliability of differentiating adnexal masses had sensitivity of 91.7% and specificity of 77.7%. Using Caruso score alone we had sensitivity of 83.3% and specificity of 88.9%. Using Sassone and Caruso score together we had sensitivity of 90.9% and specificity of 93.3%. Conclusion: In evaluation of adnexal masses combining both sonomorphological and color Doppler scores which gave higher specificity and positive predictive value (PPV) than using individual score alone.